Exploring the synergistic mechanism of Gegen Qinlian Decoction on the Wnt signaling pathway using an integrated strategy of network pharmacology and RNA-seq. (5th October 2021) - Li, Yanping; Gong, Yiting; Zhang, Xin; Wang, Jiaxin; Cheng, Yaru; Liu, Fen; Shi, Xiujia; Xu, Wenjuan; Dong, Ling
Abstract: Ethnopharmacological relevance: Gegen Qinlian Decoction (GQD) (including: Puerariae lobatae (Willd.) Ohwi, radix; (short for Gengen) Glycyrrhiza uralensis Fisch., root and rhizome (short for Gancao), honeyed; Coptis chinensis Franch., rhizome (short for Huanglian); Scutellaria baicalensis Georgi, radix, boiled (short for S. baicalensis ) has been widely used to treat inflammatory bowel disease (IBD) and colorectal cancer (CRC). To explore compatibility mechanism of GQD could be of advantage to investigate the complex principle of TCM, which might be conducive to the exploration of the modernization of TCM. Aim of review: In this study, a strategy based on system pharmacology was constructed to uncover the multi-target regulation and compatibility mechanism of GQD on the Wnt signaling pathways. Material and methods: The pharmacological network of GQD was constructed by TCMSP, DAVID, Uniprote database. The cell growth inhibitory effects of puerarin (PUE), wogonin (WOG), berberine (BER), and glycyrrhetinic acid (GLY) on SW480 cells were assessed using CCK-8 assay. The multi-target regulation and compatibility mechanism of combination PUE with GLY were examined by RNA-seq, HPLC-QQQ/MS, qRT- PCR and Western blot analysis. Results: Network pharmacology analysis indicated that PUE, WOG, BER and GLY were the active components in GQD and had a synergistic effect on the targets of the Wnt signaling pathway. Additionally, pharmacological experiments revealed that WOG, BER, and GLY inhibited activity of colorectal cancer (CRC) cell lines SW480 cells, and that PUE only exhibited effective antitumour activity when combined with GLY. CTNNB1, CCND1 and SMAD4 were identified as synergistic targets inhibited by PUE-GLY. Moreover, PUE-GLY could influence the Wnt signaling pathway by upregulating GSK3B and downregulating CTNNB1 synergistically. It also showed that GLY could effectively increase the intracellular content of PUE based on HPLC-QQQ/MS analysis, and this process was achieved by influencing the targets of the membrane's pathway, such as cell adhesion molecules, focal adhesion, and tight junctions. Conclusion: GLY was revealed a multi-target mechanism, which could downregulate CTNNB1 as the active component and intervene in membrane proteins ( CDH1, CADM1, ITGB2, ICAM1, ITGA1 ) as 'guide' in the formulae. Moreover, the mechanism of synergistic antitumour action of PUE (the active component of Monarch drug) and GLY (the active component of Guide drug) on the Wnt signaling pathway was explored systematically. It was a promising breakthrough for elucidating the scientific connotation of the compatibility of TCM formulae and provide a valuable and practicable methodology for clarifying the mechanisms of TCM. Graphical abstract: Image 1